Les images d’enfermement dans John Marchmont’s Legacy de Mary Elizabeth Braddon - Marion Charret-Del Bove (Cahiers Victoriens et Edouardiens)
Mary Elizabeth Braddon’s novel John Marchmont’s Legacy was serialized in Temple Bar from December 1862 to January 1864. I am principally interested here in presenting the frequently used images of imprisonment, physical as well as social. Indeed this text allows Miss Braddon to throw light on the position of middle-class Victorian women in a patriarchal and particularly oppressive world. If, in this story, the reader can see an attempt at refusing or revolting against a paradoxical ideological discourse, Miss Braddon eventually aimed at opening women’s world by subverting traditional roles and making male protagonists experience female suffering and boredom. Intertextuality is also a powerful way of opening the text on others such as Tennyson’s ‘Mariana’ or Charlotte Brontë’s Jane Eyre and voicing a growing feeling of dissatisfaction against an imposed and inappropriate role for women.